Beckman Skylab Metabolic Gas Analyzer (1970)
A full-scale model of a gas analysis instrument made by Beckman Instruments' Advanced Technology Operations (ATO) in 1968 for the Martin-Marietta Corporation for potential use on the Skylab space station. This instrument was designed to measure astronauts' capability to perform labor during extended periods of weightlessness.
Keywords: Scientific apparatus and instruments; Skylab Program; Respiration--Measurement; Beckman Instruments, Inc.